Minimal invasive extracorporeal circulation an alternative to ECMO in ventricular tachycardia ablation - Condello Ignazio (The Journal of ExtraCorporeal Technology, 2023)
Background: The advantages of mechanical assistance during ventricular tachycardia (VT) ablation have not been clinically demonstrated. We propose and discuss a technique, set up by us, that makes use of minimally invasive extra-corporeal circulation (MiECC) type III associated with a venous reservoir system, which allows complete cardiac flow support and blood oxygenation as well as hemodynamic stability during long-lasting procedures. Methods: We present a retrospective case series of ten patients with valvular heart disease and unresponsive Ventricular Tachycardia (VT) who underwent VT ablation with MiECC support. The mean age of the patients was 72 ± 8 years and the left ventricular ejection fraction was 36 ± 12%. All patients underwent a clinical evaluation to identify the cause of VT unresponsiveness (e.g., ischemic heart disease). Results: A total of 140 min, the following parameters were evaluated and recorded for 140 min. Central venous pressure (CVP) was used to evaluate excess volume. During the first 5 min, the mean was 15 mmHg, with a pump flow of 1.5 L/min and a mean systemic arterial pressure of 100 mmHg while setting up the circulation support. Following drainage in a volumetric bag of 1 L of blood, CVP was reduced to a value of 5 mmHg with a flow rate of 5 L/min and a mean systemic arterial pressure of 65 mmHg. In the case of small and low-weight patients our “1 L protocol” can be modified. Conclusions: In this preliminary retrospective case series, the MiECC type III system may represent the ideal support system during VT ablation, and further studies are needed to support this preliminary report.